KEANEKARAGAMAN JENIS VEGETASI PENYUSUN TEMBAWANG DI DESA BANGUN SARI KECAMATAN TERIAK KABUPATEN BENGKAYANG - wandi, .; Ekamawanti, Hanna Artuti; Widiastuti, Tri (JURNAL HUTAN LESTARI, 2016)
Tembawang is one of the efforts to preserve the species biodiversity. However, ecosystem in the tembawang can be damaged and change because of interference from human activities, such as shifting cultivation, timber extraction for building materials and other activities that could severely affect species diversity of vegetation in it. This research aims to obtain information on the diversity of the dominant vegetation species of the tembawang in the Bangun Sari village of Teriak Subdistrict, Bengkayang Regency. The method used in this research was survey method with a combination of combined methods of transect and plot line. Observation were made in five transects with a total of 52 observation plots, so the total area of observation location is a 2.08 ha. Based on the research, there are at least 91 species of vegetation from 34 families identified in the tembawang in Bangun Sari village. The Shannon-Wiener diversity index analysis shows that the level of vegetation species diversity that froms tembawang in Bangun Sari village was categorized as moderate (H’1≤ H’≤ 3). Overall the most dominant species in the tembawang are jackfruit, durian, rubber, langsat and terap. These species belong to the top ten highest important value index that appears in each level of growth. Keywords:       Bangun Sari village, Dominant species and important value index, Species biodiversity, Tembawang.